2004
DOI: 10.1001/archsurg.139.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Malignant Intraductal Papillary Mucinous Tumors of the Pancreas

Abstract: Background: The accurate differential diagnosis of malignant intraductal papillary mucinous tumors (IPMTs) of the pancreas from benign IPMTs remains unclear. Hypothesis: Predictive factors for differentiating malignant IPMTs from benign IPMTs can be documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 29 publications
5
55
1
Order By: Relevance
“…Currently, however, there are no laboratory markers that can adequately detect IPMNs or differentiate between benign and malignant IPMNs. Conventional cytologic analysis of pancreatic tissue and serum CA19-9 levels are commonly used in the clinical setting, but they are not able to differentiate between benign and malignant IPMNs (41,42). The identification and characterization of overexpressed genes as well as underexpressed genes in IPMNs might allow us to identify clinically relevant biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, there are no laboratory markers that can adequately detect IPMNs or differentiate between benign and malignant IPMNs. Conventional cytologic analysis of pancreatic tissue and serum CA19-9 levels are commonly used in the clinical setting, but they are not able to differentiate between benign and malignant IPMNs (41,42). The identification and characterization of overexpressed genes as well as underexpressed genes in IPMNs might allow us to identify clinically relevant biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Sohn et al [22] reported that there appears to be a lag time of approximately 5 years in the progression from adenoma to invasive carcinoma and that progression to invasive carcinoma occurs relatively quickly once moderate dysplasia is found. Kawai et al [17] reported that the malignancy rate of IPMNs was 48% while it was 67% in the study conducted by Lopez Hänninen et al [23] . In our study, the malignancy rate was 60% (12 of 20).…”
Section: Discussionmentioning
confidence: 94%
“…The IPMN can evolve through all biological stages, from slight dysplasia to carcinoma. As one of the few surgically curable pancreatic tumors, accurate preoperative prediction of malignancy remains one of the major issues in the optimal treatment of IPMNs, and it also influences the outcome of the resection [16,17] . The present study retrospectively assessed the imaging findings of IPMNs with MDCT and evaluated the capabilities of MDCT with emphasis on the postprocessing techniques to predict the malignancy of IPMNs.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of CCR7 expression with regard to the presence of lymph node metastases was quantified via a receiver operating characteristic (ROC) analysis (24,25). The associations between CCR7 expression and clinicopathological features were evaluated by either the ¯2 test or Fisher's exact test as appropriate.…”
Section: Discussionmentioning
confidence: 99%